Tingkat Kekeruhan Kadar Vitamin C dan Aktivitas Antioksidan Infused Water Lemon Dengan Variasi Suhu Dan Lama Perendaman - Indah Trisnawati; wikanastri hersoelistyorini; nurhidajah nurhidajah (Universitas Muhammadiyah Semarang, 2019)
Lemon is a fruit that is rich in vitamin C. The processing of lemon as an infused water is one way to get optimal benefits from lemon. Lemon infused water is treated by soaking it in water for several hours. The temperature and soaking time are thought to influence the physical and chemical characteristics of lemon infused water. This study aims to determine the level of turbidity, vitamin C and antioxidant activity of lemon infused water. This study used a completely randomized design of two factors, with two differences in temperature (refrigerator temperature and room temperature) and five differences in soaking time (1, 2, 3, 4, 5 hours) and then analyzed turbidity levels, vitamin C levels and antioxidant activity. Observation data were analyzed using Two Way Anova. The results showed turbidity, vitamin C, and antioxidant activity at room temperature were higher than the refrigerator temperature and the longer soaking the turbidity level, vitamin C, and antioxidant activity were also as high as possible. The results of the analysis of variance showed that there were effects of temperature and soaking time on the level of turbidity and vitamin C of lemon infused water but there was no effect of soaking time on antioxidant activity. Soaking time at room temperature for 1 hour or at refrigerator temperature for 4 hours is the best time to get optimum vitamin C and antioxidant activity.